Blast tests and FEA calibration - Del Linz, Paolo (Nanyang Technological University, 2020)
This document mostly reports on the efforts to determine whether the steel and sandwich structures were affected by the combined blast and fragment loading to the same extent as was seen for the RC structures. Of especial importance was to determine whether the impacts, besides transmitting significant momentum to the system, also affected its overall stiffness and capacity due to the localized damage. To achieve this, blast tests and quasi static tests were performed and modeled.